ANALISIS PENGAMBILAN KEPUTUSAN INVESTASI UNTUK MERAIH PROFIT KONSISTEN PADA PASAR UANG ONLINE (Studi Pada Lembaga Pendidikan dan Pelatihan Kerja – LPPK Financial Education, Nganjuk) - prasetya tri mahendra (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2014)
The continued development of information technology to encourage various parties to compete in fulfilling the needs of both physical and non-physical. Market as the fulfillment of human needs from the first until now always been growing rapidly, ranging from market goods, services market, the labor market to the capital market and money market. Exchange or money market is still very dominate the world market, as technological developments for today's financial markets can be done with the online system, plus the application of the concept of sharia / non usury / interest for the non-Muslim perpetrators of the majority in Indonesia. Corresponding description of the background in front of which has been delivered, we can formulate the problem of this research, namely: How good decision making in investment to get a consistent profit on the internet online money market trading? By using both Technical Analysis / mathematical analysis and supported by fundamentals, then investing in a money market alternative benefit / profit in addition to the public revenue. Besides, the application of the business need for mentors, to provide training online currency trading. Because they factor of trading psychology and money management is also a major thing for critical success trading these currencies online.